Service-Learning as a Novelty Experience at Central and Eastern European Universities: Students’ Narratives of Satisfaction and Premises of Change - Ilić, Bojana Ćulum; Brozmanová Gregorová, Alžbeta; Rusu, Alina Simona (Frontiers in Education, 2021)
As a proxy of community-engaged teaching and learning pedagogy in higher education institutions (HEIs), service-learning (SL) has just recently become a phenomenon of research and policy interest in the European Higher Education Area (EHEA). This study explores the first-ever service-learning experience of 246 students coming from three universities at Central and Eastern Europe (Slovakia, Romania and Croatia). Research findings speak in favour of students’ satisfaction with their first-ever SL experience, regardless of the country of their residence. Students from all three countries highly value their SL experience as it provided them with possibilities to learn a lot about the academic field and community as well, by facilitating their personal and professional contribution to the community. The legacy of SL courses relates with paradigmatic shifts in various academic aspects, like students and professors changing roles, students being placed in the centre of the learning process, connectedness of the curricula with the real-life setting, better understanding and appreciation of subjects studied. As for the non-academic related aspects, students’ reflection disclose their acknowledgment of personal growth and changes related with cognitive, emotional and behavioural dimensions. Our findings reveal that the unique experience students had with the SL courses shaped their narratives into ones of satisfaction, empowerment and change.